1976
DOI: 10.1111/j.1751-1097.1976.tb06817.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitization of Human Diploid Cell Cultures by Intracellular Flavins and Protection by Antioxidants

Abstract: Abstract— The damaging effects of near ultraviolet and visible light on WI‐38 human diploid lung fibroblasts were investigated. WI‐38 cells in culture were killed by light doses ranging from 2 to 10 × 103 W/m2 h. There was an inverse correlation between culture age, i.e. population doubling level and photosensitivity. However, this effect could not be related to capacity for DNA synthesis and cell division. Flavins were clearly implicated as endogenous photosensitizers, and antioxidants such as d, l‐α‐tocopher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Previous studies have shown that irradiation of mammalian cells with violet or blue light induced H 2 O 2 production and DNA damage (1)(2)(3)(4)(5)(6)(7)(8)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Catalase and other antioxidants prevented this damage, indicating that H 2 O 2 production was a critical, early step in the process.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that irradiation of mammalian cells with violet or blue light induced H 2 O 2 production and DNA damage (1)(2)(3)(4)(5)(6)(7)(8)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Catalase and other antioxidants prevented this damage, indicating that H 2 O 2 production was a critical, early step in the process.…”
mentioning
confidence: 98%
“…Less recognized or understood is that toxicity can be induced by visible light. Specifically, violet (400-450 nm) and blue (450-490 nm) light are known to cause mutations and even death of cultured mammalian cells at irradiation doses of 2-6 J/cm 2 (1)(2)(3)(4)(5)(6)(7)(8), which is equivalent to 5-10 min of direct sunlight (9). Although most human cells are protected from sunlight by physical barriers (skin, hair, clothing), clinical pathologies resulting from intense sources of violet-blue light have been reported, e.g., solar retinopathy (10,11) and erythropoietic protoporphyria (12,13).…”
mentioning
confidence: 99%
“…WI-38 human fibroblasts show a gradual decline m growth rate with exposure to visible light [6] with younger cells bemg more susceptrble to photokilling and with partial protection observed by DL-o-tocopherol or vitamin E. Visible lightabsorbing chromophores and vitamin E are largely associated with the inner mltochondnal membrane. A previous study made on the effect of visible light exposure to isolated mrtochondna has indicated a flavin-photosenatized mitration process and oxygendependent damage to energy coupling, flavm dehydrogenases and quinones, but not to hemoproteins of the inner membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Such concerns seem justified in view of DNA modifying activity of phototherapy (9), a property shared with many chemical carcinogens and teratogens (1). The photodynamic damage of intracellular DNA has been well characterized and is enhanced by, but not dependent upon, the presence of exogenous photosensitizing agents (3,7,10,11). Such enhancement takes on clinical significance when it is realized that many low birth-weight infants receiving phototherapy are simultaneously administered parenteral hyperalimentation solutions containing photosensitizers, i.e., multivitamins, amino acids, etc.…”
mentioning
confidence: 99%